Effectiveness of Using PinterPolitik.TV’s Youtube Channel in Strengthening the Character of Nationalism - Rezaldi, Mohammad Rizky; Syaharuddin, Syaharuddin; Nadilla, Dewicca Fatma (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to determine the effectiveness of using the PinterPolitik.TV YouTube channel to strengthen students’ nationalism character in learning class XI history at SMAN 7 Banjarmasin. The research method used a quantitative approach and descriptive research. The sampling in this study used probability sampling with a simple random sampling technique. The data collection technique used in this research was a questionnaire. The reference for measuring the use of the PinterPolitik.TV YouTube channel uses Information Systems Success Theory as an indicator for the independent variable and the Character of Nationalism as an indicator for the dependent variable. Data collection was conducted by distributing physical questionnaires to 167 respondents. The results of research from 167 respondents on 26 statement items related to the effectiveness of using the PinterPolitik.TV YouTube channel on strengthening the character of student nationalism in learning history obtained a significance result of 0.000, which is smaller than 0.05. The total measurement of the effectiveness of using the PinterPolitik. TV YouTube channel on strengthening the character of student nationalism is 65.00%, which is included in the Success category.